A localization method for extraction of foreign matter in the myometrium. Issue 1 (6th August 2021) - Han, Ling; Shi, Gang; Ruan, Jiaying
Synopsis: The present case report supports the use of a localization method for identifying and extracting foreign matter in the myometrium. This method has many advantages such as ease of administration, sound effectiveness, lessened trauma, reduced expenses, and rapid rehabilitation.